Extending point pattern analysis for objects of finite size and irregular shape - WIEGAND, THORSTEN; KISSLING, W. DANIEL; CIPRIOTTI, PABLO A; AGUIAR, MARTÍN R (The Journal of ecology, 2006)
1 We use a grid- and simulation-based approach to extend point pattern analysis to deal with plants of finite size and irregular shape, and compare the results of our approach with that of the conventional point approximation. The plants are approximated by using an underlying grid and may occupy several adjacent grid cells depending on their size and shape. Null models correspond to that of point pattern analysis but need to be modified to account for the finite size and irregular shape of plants. 2 We use a mapped area of a grass-shrub steppe in semi-arid Patagonia, Argentina, to show that the shrub community is essentially randomly structured, but that shrubs facilitate grasses in their immediate neighbourhood. 3 The occurrence of this random spatial structure provides important new information on the biology of shrub populations. In general, previous data from semi-arid and arid ecosystems have shown that adult shrubs tend to show over-dispersed patterns, whereas juveniles are clumped. 4 We find that the point approximation may produce misleading results (i) if plant size varies greatly, (ii) if the scale of interest is of the same order of magnitude as the size of the plants, and (iii) if the plants of a given pattern are constrained through competition for space by the presence of other plants. The point approximation worked well in all other cases, but usually depicted weaker significant effects than when the size and shape of plants were taken into account. 5 Our approach to quantifying small-scale spatial patterns in plant communities has broad applications, including the study of facilitation and competition. Ecologists will be able to use the software available to take advantage of these methods.